Cohomological $χ $ -dependence of ring structure for the moduli of one-dimensional sheaves on $\mathbb {P}^2$ - Woonam Lim; Miguel Moreira; Weite Pi (Forum of Mathematics, Sigma, 2024)
We prove that the cohomology rings of the moduli space